Role of p57KIP2 in Stem and Progenitor Leydig Cells of Mouse Testes - Seung Hyun Park; Kyung Noh Yoon; Yang Xu; Myung Chan Gye (The World Journal of Men's Health)
Purpose: Precise control of proliferation and differentiation of Leydig cells is important for gonadal androgenesis and spermatogenesis. Though cyclin-dependent kinase inhibitors are crucial for cell proliferation and differentiation, their role in the development of early adult Leydig cells (ALCs) remained unanswered. To understand mechanism for ALC development, functional expression of p57KIP2 (cdkn1c) was investigated in the stem Leydig cells (SLCs) and progenitor Leydig cells (PLCs) in mice. Materials and Methods: The roles of p57KIP2 in the proliferation, differentiation, apoptosis, and steroidogenesis in SLCs and PLCs were investigated by antibodies and bromodeoxyuridine (BrdU) labeling in the early neonatal testes and p57kip2 siRNA in the isolated SLCs and PLCs. Steroidogenic differentiation of PLCs was examined by progesterone and testosterone production in cell culture. Results: From postnatal day (PND) 1 to 14, p57KIP2(+) spindle-shaped cells in the testis interstitium were α-smooth muscle actin (αSMA)(-), a peritubular myoid cells marker, suggesting that they are SLCs and PLCs. Besides, p57KIP2 was also expressed in HSD3β(+) fetal Leydig cells. From PND1 to 14, BrdU(+)/αSMA(-), Ki67(+)/p57KIP2(+), and BrdU(+)/p57KIP2(+) spindle-shaped cells were gradually decreased. From PND1 to 14, p57KIP in the αSMA(-)/p57KIP2(+) cells was peaked at PND7 and decreased thereafter. In THY1(+) isolated SLCs, p57kip2 siRNA significantly increased ki67 and pcna mRNA and pdgfrα mRNA, a differentiation marker and decreased nestin mRNA, a SLC marker. No significant difference in apoptosis related genes mRNA was found after p57kip2 siRNA treatment. In HSD3β(+) PLCs, p57kip2 siRNA increased proapoptotic genes mRNA, annexin V(+) early-apoptotic cells. Importantly, p57kip2 siRNA significantly decreased hsd3β6 and cyp17a1 mRNA and progesterone production. Conclusions: p57KIP2 may suppress proliferation and support stemness of SLCs. In PLCs, p57KIP2 may suppress apoptosis and potentiate the steroidogenic differentiation.